International Wrongful Act - Sferrazza Taibi, Pietro (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
This paper will deal with a dogmatic analysis of the notion of internationally wrongful acts within the framework of the international responsibility of the State. Undoubtedly, this is a key notion, since its configuration in one case activates the functionality of the rest of the chapters of the State’s international responsibility. The paper will explain the impact of the distinction between primary and secondary rules for the construction of the concept of internationally wrongful act. It will also address an analysis of each of the two constituent elements of the internationally wrongful act, namely, breach and attribution.